Cover Picture: Durable Nickel‐Iron (Oxy)hydroxide Oxygen Evolution Electrocatalysts through Surface Functionalization with Tetraphenylporphyrin (Angew. Chem. Int. Ed. 51/2022) - Kang, Sinwoo; Im, Changbin; Spanos, Ioannis; Ham, Kahyun; Lim, Ahyoun; Jacob, Timo; Schlögl, Robert; Lee, Jaeyoung (Angewandte Chemie International Edition, 2022)
State‐of‐the‐art nickel–iron oxyhydroxide catalysts suffer from loss of iron under oxygen evolution reaction (OER) potential. In their Research Article (e202214541), Jaeyoung Lee and co‐workers develop a stable OER electrocatalyst by adding tetraphenylporphyrin protective layers. They accelerate the redeposition of eluted iron onto the electrocatalyst by forming a nonpolar–polar interface. This not only prolongs the iron population but also the lifetime of the electrocatalyst.